MODERN PROBLEMS OF THE COURSE OF “TECHNOLOGY FOR THE DECORATIVE PROCESSING OF MATERIALS” - M. L. Sokolova (Российский технологический журнал, 2017)
The paper analyzes development of the "Technology for the decorative processing of materials" course for students. The course was created in 1992 in order to train personnel competent both in the field of design and in that of materials science. The paper treats the conditions of teaching students in the present and the prospects of graduates’ activities. On this basis, the academic and scientific problems which need to be solved for the successful future development of the course have been defined. The academic problems comprise the following points: selection of university entrants specializing in the field, training of the students in the process of working on interdisciplinary projects, determination of the spheres of scientific research for the master course students with the aim of providing their professional growth. Among the scientific aspects of the course development are considered, firstly, the problems of adaptation of modern technologies for the individual production which does not require special production conditions (great power, additional personnel, specialized spaces). Secondly, problems which the graduates of the "Technology for the decorative processing of materials" course would have to face in the process of creating fundamentally new objects by way of filling traditional forms with new electronic contents (“smart” electronics), or in the process of forming “smart”, comfortable and accessible environment. Special treatment is given to the problems connected with the universal design which must also be a field of expertise for the present-day course graduates. The paper suggests ways of solving the stated problems on the basis of the modern society’s demands towards science and education, in particular on the basis of expert analysis of products and environments from the positions of the universal design.